Making anemia education media through the “getaran garpu tala” program for junior high school students at the Tempel I Community Health Center in catchment areas during the COVID-19 pandemic - Diana Citrasari (BKM Public Health and Community Medicine, 2021)
Objectives: This activity aims to provide anemia education media through the Getar Thala program (Gerakan Tanggulangan Anemia and Thalassemia) during the pandemic, increasing the knowledge of junior high school (SMP) students in Turi about anemia and improving adherence to taking blood-supplementing tablets (TTD). Contents: the media that has been created are videos and educational leaflets used during the Covid-19 pandemic and delivered online. This educational media will facilitate online education for Puskesmas officers in introducing the Getar Thala program, which has been prepared by the Sleman District Health Office in 2019. Educational services can be delivered through the school’s WhatsApp group social media, the Zoom Meeting application, or the Google Meet application. Through these media, we hope it can increase the knowledge of high school students in the working area of ​​the Tempel I Health Center about anemia and increase the compliance of adolescent girls in consuming blood-added tablets.